PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DENGAN PENERAPAN PEDOMAN AKUNTANSI SEBAGAI VARIABEL PEMEDIASI - Ika Putri, L. P. Novyanti Ciptana; Dharma Suputra, I D. G.; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.09.TAHUN 2015, 2016)
Accounting standards and guidelines used by Bank Perkreditan Rakyat (BPR) aims to generate a comparable financial information. This study aims to demonstrate empirically the effect of implementation of SAK ETAP toward BPR’s financial performance with the application of PA-BPR as a mediating variable in Gianyar. The populations in this study were all BPR that are operating in Gianyar regency in 2013. Samplings were selected based on the saturated sample method, which is using all the population as the respondents. The sample in this study is as much as 28 BPR with 91 respondents. The data were analyzed using Path Analysis. The results showed that: 1) the implementation of SAK ETAP effected the BPR’s financial performance; 2) the implementation of SAK ETAP effected the application of PA BPR; 3) the application of PA-RB effected the BPR’s financial performance in Gianyar; 4) the implementation of SAK ETAP effected the BPR’s financial performance in Gianyar with the application of PA-BPR as a mediating variable.
Keywords: SAK ETAP, PA BPR, Kinerja Keuangan BPR